Low-carbon treatment of zinc contaminated iron tailings using high-calcium geopolymer: Influence of wet-dry cycle coupled with acid attack. (1st March 2022) - Wei, Mingli; Li, Yuan; Yu, Bowei; Wei, Wei; Liu, Lei; Xue, Qiang
Abstract: Zinc contaminated iron tailings can be stabilized by an environmentally friendly high-calcium geopolymer as a new filler material for clean reutilization. The durability and toxic leaching of stabilized materials are vital for sustainable engineering applications, especially when exposed to complex environments. This study comprehensively studied the strength and leaching performance of four types of high-calcium geopolymer stabilized tailings (M series and C series; M1, M2, C1, and C2) subjected to the erosion of the Wet-Dry cycles coupled with Acid rain (WDA). Tests including unconfined compression test, apparent integrity, and mercury intrusion test were carried out to evaluate the strength and durability of stabilized tailings. These results showed that the erosion resistance of the C series was worse than that of the M series. Meanwhile, the leachate properties, e.g., pH, electrical conductivity, and typical ion (calcium, magnesium, and zinc) leaching concentrations, were examined to evaluate the leaching durability of the stabilized tailings. The relationships between chemical properties and ion leaching concentration were analyzed, which helped understand the erosion and leaching mechanisms. These results reflected that the occurrence of erosion is due to the coupling effect between the structural damage and hydration reaction. Furthermore, the stabilized materials after the WDA erosion were investigated the mechanisms of immobilization, erosion, and leaching via the X-ray diffraction and scanning electron microscope-energy dispersive spectroscopy tests. The mechanisms of zinc immobilization were precipitation, adsorption and solid-solution structure, and physical encapsulation. After the WDA erosion, the number of hydration products would decrease, but the zinc-sulfate precipitates would increase to reduce zinc leaching. Therefore, the increase of zinc leaching concentration was related to zinc desorption and damage of physically encapsulated zinc. The paper deepens the understanding of the durability of these stabilized materials under wet-dry and acid erosion, improving the reuse reliability of clean and green materials. Graphical abstract: Image 1 Highlights: Using one-part high-calcium geopolymer made from waste to stabilize Zn-based tailing. CGTs are surface erosion, the 4th or 5th cycle is a damaged node. M series have the best resistance because Mg-based products improve the performance. Sulfate erosion might produce Zn-SO4-H and bianchite, which can resist erosion. Zn leaching is mainly caused by desorption and encapsulation destruction.